Analisis Tebal Perkerasan Lentur Menggunakan Metode AASHTO 1993 - Muhammad Djaya Bakri (Borneo Engineering : Jurnal Teknik Sipil, 2020)
Every year there is an increase in the number of students at the Universitas Borneo Tarakan, which naturally requires the addition of campus buildings, including the construction of road infrastructure to support the development of the campus area. This study aims to analyze the needs of the thickness of the new flexible road pavement construction in the campus area by using the AASHTO 1993 method. This method requires a Structural Number (SN) value that can be calculated by nomogram method and trial and error method. The results of the nomogram method get the value of SN total = 2.09 inches, SN2 = 1.59 inches, and SN1 = 1.39 inches, and the trial and error method gets the value of SNTotal = 2.05 inches, SN2 = 1.56 inches, and SN1 = 1.36 inches. To avoid the risk factor of estimating the error of repetition of traffic loads during the life of the plan (W 18), in the calculation of the SN value, the trial and error method needs to include the value of FR (reliability factor) in the calculation of w18 , where the value obtained FR = 2.39 and W18 = 0, 11x10 6 ESAL. Analysis of the thickness of the flexible pavement construction layer using SN values calculated by the nomogram and trial and error method, resulting in a 39 cm thick flexible pavement, with a surface course = 9 cm, sub-base course = 15 cm, and a base course = 15 cm.